2009
DOI: 10.2337/db09-0911
|View full text |Cite
|
Sign up to set email alerts
|

A Central Role of RLIP76 in Regulation of Glycemic Control

Abstract: OBJECTIVEPathology associated with oxidative stress frequently results in insulin resistance. Glutathione (GSH) and GSH-linked metabolism is a primary defense against oxidative stress. Electrophilic lipid alkenals, such as 4-hydroxy-t-2-nonenal (4HNE), generated during oxidative stress are metabolized primarily to glutathione electrophile (GS-E) conjugates. Recent studies show that RLIP76 is the primary GS-E conjugate transporter in cells, and a regulator of oxidative-stress response. Because RLIP76−/− mice ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
56
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 32 publications
(61 citation statements)
references
References 46 publications
5
56
0
Order By: Relevance
“…In contrast, the insulin/ glucose ratio was lower and did not change significantly from baseline in the RLIP76 Ϫ/Ϫ mice fed a HFD. These results confirm peripheral and hepatic insulin sensitivity of the knock-out mice in glucose-clamp studies (42), and indicate that genetic loss of RLIP76 nearly completely prevents HFD-induced obesity and insulin resistance. Glucose tolerance was significantly impaired in RLIP76 ϩ/ϩ mice given a HFD as compared with RLIP76 Ϫ/Ϫ mice (Fig.…”
Section: Rlip76 ϫ/ϫ Mice Are Resistant To Hfd-induced Weight Gain-supporting
confidence: 75%
See 4 more Smart Citations
“…In contrast, the insulin/ glucose ratio was lower and did not change significantly from baseline in the RLIP76 Ϫ/Ϫ mice fed a HFD. These results confirm peripheral and hepatic insulin sensitivity of the knock-out mice in glucose-clamp studies (42), and indicate that genetic loss of RLIP76 nearly completely prevents HFD-induced obesity and insulin resistance. Glucose tolerance was significantly impaired in RLIP76 ϩ/ϩ mice given a HFD as compared with RLIP76 Ϫ/Ϫ mice (Fig.…”
Section: Rlip76 ϫ/ϫ Mice Are Resistant To Hfd-induced Weight Gain-supporting
confidence: 75%
“…RLIP76 Ϫ/Ϫ Mice Are Resistant to HFD-induced Hyperlipidemia-Hyperlipidemia is a key pathological component of MetS as well as obesity. We have previously shown that, in addition to BG, both serum cholesterol and triglycerides are also considerably lower in RLIP76 Ϫ/Ϫ mice (42,43). Results of the present studies (Fig.…”
Section: Rlip76 ϫ/ϫ Mice Are Resistant To Hfd-induced Weight Gain-supporting
confidence: 70%
See 3 more Smart Citations